Hadith #1943 - Sunan al-Nasa'i - Ahmed bin Bkar bin Aby أحمد بن بكار بن أبي; al-Mughira ibn Shu'ba; Bashr bin al-Sari al-Afwah بشر بن السري أبو عمرو الأفوه; Jubayr bin Hayya al-Thaqafi; Ziyad bin Jubayr bin Hiyya زياد بن جبير بن حية (Sunan al-Nasa'i)
“The believer owes six duties toward his fellow believer: To visit him when he is sick, to attend his funeral when he dies, to accept his invitation, to greet him with Salam when he meets him, to reply to him (say: Yarhamuk Allah, may Allah have mercy on you) when he sneezes and to be sincere to him, whether he is absent or present.” (Hasan).
Grade:

Hadith #1948 - Sunan al-Nasa'i - al-Mughira ibn Shu'ba; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Jubayr bin Hayya al-Thaqafi; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Sa'id bin 'Ubaid al-Tai'i سعيد بن عبيد الطائي; Ziyad bin Jubayr bin Hiyya زياد بن جبير بن حية (Sunan al-Nasa'i)
“The Messenger of Allah said: “The rider should travel behind the Janazah and the pedestrian may travel wherever he wishes, and the (funeral) prayer should be offered for a child.”‘
Grade:

Hadith #3179 - Sunan Abi Dawud - al-Mughira ibn Shu'ba; Jubayr bin Hayya al-Thaqafi; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد; Ziyad bin Jubayr bin Hiyya زياد بن جبير بن حية (Sunan Abi Dawud)
I saw the Prophet (ﷺ) and Abu Bakr and Umar walking before the funeral.
Grade: Sahih

Hadith #1029 - Jami' al-Tirmidhi - al-Mughira ibn Shu'ba; Bashr bin Adam al-Dareer بشر بن آدم الضرير; Jubayr bin Hayya al-Thaqafi; Ziyad bin Jubayr bin Hiyya زياد بن جبير بن حية (Jami' al-Tirmidhi)
The Prophet said: “No one among the Muslim dies, and Salat is performed for him by a community of Muslims reaching one hundred, and they intercede (supplicate) for him, except that their intercession for him is accepted.” In his narration, ‘Ali bin Hujr said: “One hundred or more than that.”
Grade: